Adenovirus Core Protein VII Downregulates the DNA Damage Response on the Host Genome - Avgousti, Daphne C. (J Virol, 2017)
Viral manipulation of cellular proteins allows viruses to suppress host defenses and generate infectious progeny. Due to the linear double-stranded DNA nature of the adenovirus genome, the cellular DNA damage response (DDR) is considered a barrier to successful infection. The adenovirus genome is packaged with protein VII, a virally encoded histone-like core protein that is suggested to protect incoming viral genomes from detection by the cellular DNA damage machinery. We showed that protein VII localizes to host chromatin during infection, leading us to hypothesize that protein VII may affect DNA damage responses on the cellular genome. Here we show that protein VII at cellular chromatin results in a significant decrease in accumulation of phosphorylated H2AX (γH2AX) following irradiation, indicating that protein VII inhibits DDR signaling. The oncoprotein SET was recently suggested to modulate the DDR by affecting access of repair proteins to chromatin. Since protein VII binds SET, we investigated a role for SET in DDR inhibition by protein VII. We show that knockdown of SET partially rescues the protein VII-induced decrease in γH2AX accumulation on the host genome, suggesting that SET is required for inhibition. Finally, we show that knockdown of SET also allows ATM to localize to incoming viral genomes bound by protein VII during infection with a mutant lacking early region E4. Together, our data suggest that the protein VII-SET interaction contributes to DDR evasion by adenovirus. Our results provide an additional example of a strategy used by adenovirus to abrogate the host DDR and show how viruses can modify cellular processes through manipulation of host chromatin. IMPORTANCE The DNA damage response (DDR) is a cellular network that is crucial for maintaining genome integrity. DNA viruses replicating in the nucleus challenge the resident genome and must overcome cellular responses, including the DDR. Adenoviruses are prevalent human pathogens that can cause a multitude of diseases, such as respiratory infections and conjunctivitis. Here we describe how a small adenovirus core protein that localizes to host chromatin during infection can globally downregulate the DDR. Our study focuses on key players in the damage signaling pathway and highlights how viral manipulation of chromatin may influence access of DDR proteins to the host genome.